1936
DOI: 10.1042/bj0302273
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light on the vitamin C of milk

Abstract: IN estimating vitamin C chemically in milk by the method of Birch et al. [1933], Kon [1933] observed very marked fluctuations in the concentration of that vitamin from day to day.The possible causes of this phenomenon were investigated by Mattick & Kon [1933], who ultimately found that milk which originally gave a positive vitamin C titration failed to reduce the indophenol reagent after a short exposure to light in glass bottles. Some time later Booth & Kon [1934] showed that 90 % of the original power of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1938
1938
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Solutions of pure crystalline ascorbic acid showed similar behavior on irradiation followed by reduction with H,S. The work of Kon and Watson (1936), which appeared during this investigation, confirms the statement as to the oxidative nature of the destruction of ascorbic acid by ultra-violet irradiation. An increase in the acidity of the juice failed to produce any change in the reducing properties.…”
supporting
confidence: 81%
“…Solutions of pure crystalline ascorbic acid showed similar behavior on irradiation followed by reduction with H,S. The work of Kon and Watson (1936), which appeared during this investigation, confirms the statement as to the oxidative nature of the destruction of ascorbic acid by ultra-violet irradiation. An increase in the acidity of the juice failed to produce any change in the reducing properties.…”
supporting
confidence: 81%
“…Hand, Guthrie & Sharp (1938) demonstrated that removal of O 2 from pasteurized milk by controlled vacuum treatment, and its subsequent exclusion, prevented flavour defects due to oxidation and preserved the reduced ascorbic acid naturally present or added to milk. Kon & Watson (1936) had previously demonstrated the latter effect. Ford et al (1969) have shown that in ultra-high-temperature (UHT) treated milk processed by direct heating and containing less than 0-1 ppm of O 2 both ascorbic acid and folic acid were retained during storage.…”
mentioning
confidence: 84%
“…It may be observed in this connexion that the slightly increased decomposition of ascorbic acid recorded by Kon & Watson [1936] when milk was exposed in quartz rather than in glass vessels, was presumably due to the direct action of ultraviolet light. The greater part of the decomposition of the acid in the quartz vessel was, however, brought about probably in the same way as in the glass vessel, namely, as suggested by Hopkins [1938], by the action of visible light sensitized by the lactoflavin of the milk.…”
Section: Without Lactoflavinmentioning
confidence: 79%
“…Martini & Bonsignore [1934] found that i-ascorbic acid reduced methylene blue to its leuco base when exposed to the light of an ordinary electric lamp. Kon & Watson [1936] observed that on exposure to visible light of short wave length (blue and violet) I-ascorbic acid in milk was oxidized to dehydroascorbic acid. A probable explanation for this phenomenon is found in the observation made by Hopkins [1937; 1938] that lactoflavin and to a lesser extent lumichrome could act as sensitizers in the oxidation of i-ascorbic acid when exposed to solar radiation.…”
mentioning
confidence: 99%